Hryhoriy Skovoroda on heavenly and earthly mountains - Krysa, Bohdana (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The image-symbol of mountain, a key image-symbol in Skovoroda’s poetical and philosophical discourse never was an object of special attention, thus making the article relevant.It aims at an attempt to ascertain the semantic and emotional function of this image in H. Skovoroda’s spiritual space, conditioned by the correlation of the Christian written tradition with the signs of its author’s interpretation determined by the advancement towards God as an advancement towards yourself, urging to rise above ordinariness and to relinquish the world’s temptations.And at the same time, the symbol of spiritual summit matches the images of earthly mountains, with spatiality of feelings enabling the emphasis on the commensurability of the visible and the invisible, of the immanent and the transcendental.This correlation makes Skovoroda’s spiritual journey both intensely dramatic and lyrical, earthly and heavenly, and the sign of Christ’s visible Crucifixion coexists with His invisible Resurrection.The image of mountain holds an important position in Skovoroda’s world.Even the affinity or the identity the images of mountain and rock have reveals this characteristic to be the foundation and the summit at the same time, the aim and the way to that aim, to watch the earth and the heaven, the man’s and the God’s.H. Skovoroda perceives the heavenly mountain as the Wisdom of God, the place of revelation, meeting with God, announcement of His will, and the earthly mountain as the visible trace of God.The image of mountain connects the visible to the invisible, becomes an equivalent of the measure of human life. One author’s text opens another one, and all of them together path the way to the Holy Scripture because they grow from it.Along these lines, Skovoroda continues the tradition which united different authors preceding him and touched the summits of Ukrainian literature. Along these lines, Skovoroda continues the tradition which united different authors preceding him and touched the summits of Ukrainian literature. We make a conclusion that talking about mountains in Skovoroda’s sense brings about a certain reverse perspective projected on the general experience of man and the experience of reading in particular.